Injuries in triathlon: a review of the literature - Mawlichanów, Maciej; Pniak, Michał; Sieradzka, Aleksandra; Różycki, Adrian; Miklis, Paweł; Ciesielska, Aleksandra; Szerej, Krzysztof; Kot, Alicja; Wojtczak, Marta; Myśliwiec, Natalia (Quality in Sport, 2024)
Triathlon is a sport consisting of three consecutive disciplines. The popularity of this sport in the world is growing every year and in 2023 as many as 3.2 million Americans declared that they train triathlon[2]. A literature review was conducted adopting the criteria of works no older than 2003, concerning injuries in triathletes, by entering medical terms such as contusio in triathlon, triathlon injuries and health in triathlon in search engines. Studies were grouped according to the criteria adopted in them into seven sections: comparison of studies by country, epidemiology per thousand hours of training, type of injury depending on the given discipline, injury risk factors, protective factors, conclusions from studies as a recommendation for competition organizers. Survey studies and official statistics of competition organizers were analyzed. It was shown that the most frequently used coefficient was the number of injuries per thousand hours of training, the authors presented lack of agreement on the discipline during which these injuries occur, and the lack of individual characteristics of a given athlete that could expose them to injuries. However, it was indicated that the greater the experience, the greater the susceptibility to injuries. Due to the lack of a single definition of injury and the small number of standardized studies, it is currently impossible to clearly assess which injuries are the most common in athletes around the world.